2017
DOI: 10.1186/s12941-017-0231-z
|View full text |Cite
|
Sign up to set email alerts
|

Extreme diversity and multiple SCCmec elements in coagulase-negative Staphylococcus found in the Clinic and Community in Beijing, China

Abstract: BackgroundCoagulase-negative staphylococci (CoNS) are recognized as a large reservoir of staphylococcal cassette chromosome mec (SCCmec) harboured by Staphylococcus aureus. However, data of SCCmec in CoNS are relatively absent particularly in China.MethodsSeventy-eight CoNS clinical and 47 community isolates were collected in Beijing. PCR was performed to classify SCCmec types. Under oxacillin treatment, quantitative real-time reverse transcription PCR (qRT-PCR) was performed to compare mecA mRNA levels and mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 26 publications
4
19
0
Order By: Relevance
“…Moreover, S. aureus is the most common human commensal and methicillin resistant S. aureus (MRSA) is commonly implicated in both hospital-acquired as well as in community-acquired infections Recently, CNSs are also reported as the most common bacterial pathogens in the hospital air [ 14 16 ]. Moreover, it is very difficult to eradicate CNS infections due to their species diversity leading to different anti-biograms and minimum inhibitory concentration (MIC) breakpoints [ 12 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, S. aureus is the most common human commensal and methicillin resistant S. aureus (MRSA) is commonly implicated in both hospital-acquired as well as in community-acquired infections Recently, CNSs are also reported as the most common bacterial pathogens in the hospital air [ 14 16 ]. Moreover, it is very difficult to eradicate CNS infections due to their species diversity leading to different anti-biograms and minimum inhibitory concentration (MIC) breakpoints [ 12 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mecA gene is located on the staphylococcal cassette chromosome (SCC) mec element, which has been categorized into 13 types 16,17 . It was shown that NAS may harbor high diversity and unknown SCCmec elements 8,18 and new SCCmec elements have indeed been described for S. cohnii 6,19 . Determination of beta-lactam antibiotic resistance in S. aureus, a well investigated staphylococcal species, and the identification of methicillin-resistant S. aureus (MRSA) is routinely performed by cefoxitin resistance testing and detection of the mecA or mecC gene.…”
mentioning
confidence: 98%
“…Chen et al showed the multiple ccr complexes composition in CoNS strains. The authors showed the ccrAB3 and ccrAB4 genes in S. hominis and S. capitis [ 57 ]. Our study revealed not only the multiple ccr but also a combination of SCC mec cassette II and III elements in all our LRSE strains.…”
Section: Discussionmentioning
confidence: 99%